Measurements of chromospheric Mg i emission lines of zero-age main-sequence stars. (28th April 2022) - Yamashita, Mai; Itoh, Yoichi
Abstract: The chromosphere is the active atmosphere in which energetic eruption events, such as flares, occur. Chromospheric activity is driven by the magnetic field generated by stellar rotation and convection. The relationship between chromospheric activity and the Rossby number, the ratio of the rotational period to the convective turnover time, has been extensively examined for many types of stars, by using narrow chromospheric emission lines, such as the Ca ii lines and the Mg ii H and K lines. However, the stars with small Rossby numbers, i.e., stars with rapid rotations and/or long convective turnover times, show constant strengths of such lines against the Rossby number. In this study, we investigate the infrared Mg i emission lines at 8807 Å of 47 zero-age main-sequence (ZAMS) stars in IC 2391 and IC 2602 using the archive data of the Anglo-Australian Telescope at the University College London Echelle Spectrograph. After subtracting the photospheric absorption component, the Mg i line is detected as an emission line for 45 ZAMS stars, the equivalent widths of which are between 0.02 Å and 0.52 Å. A total of 42 ZAMS stars show the narrower Mg i emission lines instead of the Ca ii infrared triplet emission lines, suggesting that they are formed at different depths. The ZAMS stars with smaller Rossby numbers show stronger Mg i emission lines. The Mg i emission line is not saturated even in the saturated regime of the Ca ii emission lines, i.e., Rossby number <10 −1.1 . The Mg i emission line is considered to be a good indicator of chromospheric activity, particularly for active objects.